Microinjection of an antibody against HSP 72 in keratinocytes to study acute UV injury - Bayerl, Christiane; Jung, Ernst G. (Experimental dermatology, 1999)
First, a method of microinjection of antibodies in primary human keratinocytes in culture was established. Second, in acute UV irradiation, the physiological role of heat shock protein (HSP) 72 in keratinocytes was studied with this method. Primary human keratinocytes in culture were injected with “controls” as fluorescent dyes, phosphate buffered saline (PBS), an irrelevant secondary antibody and an antibody against a protein with known protective function in UV erythema, HSP 72. UV irradiation was applied and survival, colony forming and immunohistochemistry for injected and non-injected keratinocytes were evaluated in a time course. Puncturing the plasma membrane with injections of “controls” as FITC, PBS and the IgG anti-mouse antibody did not result in reflux of injected material or any alteration in morphology or colony-forming ability for 24 h. Keratinocytes injected with an mAb to HSP 72 without UV irradiation survived microinjection for up to 12 days, while surprisingly, more than double of injected and irradiated ones died after 12 h compared to not injected and irradiated ones. Moreover, microinjection of the antibody to HSP 72 in the nucleus resulted in a loss of the immunohistochemical labeling for HSP 72 in these cells after 12 h. Microinjection of the “controls” did not harm the survival, forming of colonies and expression of HSP 72 in keratinocytes for 24 h. In contrast, microinjection of an mAb against HSP 72 led to an increase in cell death after UV irradiation, confirming that HSP 72 is important for UV protection. Microinjection of antibodies in human keratinocytes in culture might allow the study of the physiological role of some proteins.